Factores que afectan el posicionamiento de productos en el exterior: el caso del sector floricultor antioqueño. (2016)
The export performance of a firm depends on internal and external factors. This article presents a valuation exercise of factors affecting exports of the floriculture sector of the department of Antioquia, Colombia. To this end, we have followed a method of hierarchical decisions supported by expert judgments with the help of employers, unions and institutions. The results indicate that the limited business vision, the human capital training, the internal logistics capacity of the organization and the exchange rate volatility are the main constraints the sector faces for internationalization through exports. The research findings serve as a proposal to validate a methodology that allows to prioritize the factors that influence the decisions of international expansion.